The good earth - Buck, Pearl S. (Sydenstricker) 1892-1973 (New York Pocket Books, 1958)
One of the greatest classics of our time, this is the powerfully moving story of peasant Wang Lung- of the family he founded that would one day become a powerful dynasty; of the gods he implored, sometimes with humility, sometimes with anger; and above all of the earth that sustained him, the land that he made to prosper against the ravages of nature and the savage attacks of bandit tribes.
Winner of Pulitzer award.
Keywords: Married women -- China -- Fiction; China -- History -- 1928-1937 -- Fiction; China -- Social life and customs -- Fiction